Tribomechanical Characteristics of UHMWPE Carbon Composites under Various Triboloading Conditions; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Panin S. V. Sergey Viktorovich; Alexenko V. О.; Kornienko L. А.; Ivanova L. R.; Ovechkin B. B. Boris Borisovich (2018, 2018)
Title screen